The diagnostic and prognostic significance of HOXC13-AS and its molecular regulatory mechanism in human cancer - Xiaosi Gu; Xin Hu; Sijia Zhang; Xiaoyu Zhang; Yong Wang; Lianlian Li; Lianlian Li (Frontiers in Molecular Biosciences)
HOXC13 antisense RNA (HOXC13-AS, also known as HOXC-AS5) is a long non-coding RNA that is expressed abnormally in various types of tumors and is closely related to clinical staging, clinical pathological features, and patient survival. HOXC13-AS is involved in the occurrence and development of tumors, affecting cell proliferation, migration, invasion, epithelial–mesenchymal transition, and tumor growth. This review summarizes the clinical significance of HOXC13-AS as a biomarker for human tumor diagnosis and prognosis and outlines the function and molecular regulation mechanism of HOXC13-AS in various types of cancer, including nasopharyngeal carcinoma, breast cancer, oral squamous cell carcinoma, glioma, and cervical cancer. Overall, this review emphasizes the potential of HOXC13-AS as a human tumor predictive biomarker and therapeutic target, paving the way for its clinical application.